Ovarian Brenner Tumors Revisited: Do We Have Space for Malignant Tumorsvand Methanol - Vesela Ivanova; Milen Karaivanov; Tihomir Dikov (Journal of Biomedical & Clinical Research, 2016)
We present a case of a 75-year-old female who underwent a total abdominal hysterectomy with bilateral salpingooophorectomy for an ovarian tumor. Hematoxylin-eosin- stained slides from tumor specimen revealed 1) focci of benign Brenner tumor; 2) mucinous cysts and 3) intracystic papillary projections resembling low-grade papillary transitional cell carcinoma (Grade 1-2) with squamous differentiation and comedo-type necrosis; 4) focal areas resembling noninvasive papillary transitional cell carcinoma Grade 3. Immunohistochemical investigation with a panel of antibodies (p63, p53, Ki-67, Wilms Tumor 1 - WT1, pi 6) was initiated. Areas resembling urothelial carcinoma showed diffuse nuclear positive reaction for p63 and wild-type expression of p53. Ki-67-nuclear positivity varied from less than 5% up to 30% in areas resembling high-grade urothelial carcinoma. WT1 expression was not seen. Weak but still exceeding background staining was observed in predominantly cytoplasmic fashion with few scattered positive nuclei in transitional cell nest of the benign component. No reactivity, however, was seen within the proliferative component. The histopathological diagnosis was a borderline/atypical proliferative Brenner tumor. The patient has been regularly followed up and is at present disease-free 5 years after diagnosis. In this paper, the authors describe the morphological characteristics of Brenner tumors and address some debatable issues in the light of recent immunohistochemical and molecular studies.